Financial Literacy Empowerment of Indonesia Migrant Workers in Singapore - Tarigan, Josua; Foedjiawati, Foedjiawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
The placement of Indonesian Migrant Workers (IMW) abroad is an effort to realise equal rights and opportunities for workers to obtain decent work and income. Many Indonesian migrant workers experience difficulties managing finances and obtaining relevant information in their country of work. Therefore, the purpose of the community service was to enrich the financial literacy of the migrant workers in Singapore through workshop methodology. The methodology enabled the participants to learn by doing about financial literacy. This community service stage includes analysis of partner needs, planning, implementation, and evaluation. The evaluation results show that migrant workers can prepare financial plans using a learning-by-doing model on worksheets.